Atomic Scale Control and Visualization of Topological Quantum Phase Transition in π‐Conjugated Polymers Driven by Their Length (Adv. Mater. 44/2021). Issue 44 (1st November 2021) - González‐Herrero, Héctor; Mendieta‐Moreno, Jesús I.; Edalatmanesh, Shayan; Santos, José; Martín, Nazario; Écija, David; de la Torre, Bruno; Jelinek, Pavel
Abstract : Quantum Phase Transitions As reported by Pavel Jelinek and co‐workers in article number 2104495, length control of π‐conjugated pentacene polymers leads to the observation of a topological quantum phase transition. The transition is marked by the emergence of a zero‐energy in‐gap edge state and a pseudo Jahn–Teller effect is identified as the driving mechanism.